A Rapid Fatal Outcome of Iliopsoas Hematoma: Clinical and Autopsy Findings - Alessandro Mauro Tavone MD; Gabriele Giuga MD; Andrea Attanasio MD; Giulia Petroni MD; Silvestro Mauriello MD; Francesca Cordova MD; Gian Luca Marella PhD (SAGE Publishing, 2022)
A case of massive muscular bleeding of iliopsoas resulting in lethal exsanguination is presented. The intramuscular bleeding occurred spontaneously in an old man with heart failure, presented to the emergency department after the acute onset of shortness of breath, and treated with therapeutic doses of antiplatelets and heparin to prevent thrombosis. On the sixth day of recovery, pain in the left lumbar region develops while there was a decrease in hemoglobin level. Computed tomography (CT) scan revealed a 10 × 3 cm hematoma of the left iliac muscle. The treatment was immediately stopped, but within 6 hours, the death was confirmed. The autopsy revealed that the hematoma, and its increased size since the latest imaging assessment, was the leading cause of death. Particularly in older patients with comorbidity, even in those with clotting parameters in the therapeutic range, the potential for fatal result of iliopsoas muscle bleeding should be considered. Identifying potential patience with increased risk of this complication could be important, especially in pandemic time of COVID-19, when the use of anticoagulant therapy-both for treatment and for prevention of severe disease-has become massive and addressed also to people without previous and specific pathologies.